Bahasa Arab di Era Digital: Eksistensi dan Implikasi Terhadap Penguatan Ekonomi Keumatan - Muhsin Muis (Institut Agama Islam Negeri Metro, 2020)
As long as we hold fast to the Qur'an and the Hadith in every activity of our lives, there is a role for Arabic in it. No even exception in the economic field, especially those based on Islamic law. Although lately there have been various translations into several languages, even all languages on earth, but it cannot be denied that it requires an in-depth and comprehensive understanding of Arabic before carrying out any process of translation, especially the language of the two Islamic Shari'a sources uses diction or sentence structure which cannot be easily transliterated or interpreted. Thus, as long as Muslims in this world exist, Arabic language continues to exist as well and its impact on every activity of life will always be strong, including the matter of strengthening the economic welfare